A time and opinion study of clinicians rendering complete denture service from September 10, 1990 to October 19, 1990 - Fresnosa, Arriel I.
Effective time management is of utmost importance in delivering complete denture service. This pilot study aims to establish time expenditures of clinicians working in the prosthodontic section. A time survey was conducted in the said section from September 10, 1990 to October 19, 1990. At the end of the shift all participants in the study were requested to answer an opinion survey. Thus, it has been established that the clinicians who worked in the prosthodontic section from September 10, 1990 to October 19, 1990, spent an average Total time of 75 hours and 28 minutes to accomplish one complete dental case. Their average Practical time is 42 hours and 6 minutes. They also spent a cumulative average of 69 minutes for consultation with the clinical instructor. The average time spent in delayed work is 32 hours and 41 minutes. The research has also established the presence of factors which cause delay in rendering complete denture service.